2000
DOI: 10.1046/j.1365-2583.2000.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and transcriptional expression of a leucokinin‐like peptide receptor from the Southern cattle tick, Boophilus microplus (Acari: Ixodidae)

Abstract: Leucokinins are invertebrate neuropeptides that exhibit myotropic and diuretic activity. Only one leucokinin-like peptide receptor is known, the lymnokinin receptor from the mollusc Lymnaea stagnalis. A cDNA encoding a leucokinin-like peptide receptor was cloned from the Southern cattle tick, Boophilus microplus, a pest of cattle world-wide. This is the first neuropeptide receptor known from the Acari and the second known in the subfamily of leucokinin-like peptide G-protein-coupled receptors. The deduced amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 54 publications
3
57
1
Order By: Relevance
“…Similar results have been reported elsewhere (19,37,38). The two non-insect leucokinin-like receptors (from L. stagnalis (15) and B. microplus (18)) were included in the dendrogram and were found to sit within a tightly defined clade, containing characterized examples of Drosophila tachykinin receptors (40 -42), together with novel putative genes. As leucokinins are considered to be distantly similar to tachykinins, this was clearly the group containing the strongest candidates for a leucokinin receptor.…”
Section: Identification Of a Drosokininsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar results have been reported elsewhere (19,37,38). The two non-insect leucokinin-like receptors (from L. stagnalis (15) and B. microplus (18)) were included in the dendrogram and were found to sit within a tightly defined clade, containing characterized examples of Drosophila tachykinin receptors (40 -42), together with novel putative genes. As leucokinins are considered to be distantly similar to tachykinins, this was clearly the group containing the strongest candidates for a leucokinin receptor.…”
Section: Identification Of a Drosokininsupporting
confidence: 84%
“…No leucokinin receptors have been identified in insects, although a receptor for a distantly related peptide, that shares a FxSWxamide motif with Drosokinin, has been cloned from the pond snail Lymnaea stagnalis, and was found to be a member of the GPCR superfamily (15). A further leucokinin-like receptor has been cloned in the cattle tick Boophilus microplus, and this also displays the seven-transmembrane domain structure characteristic of GPCRs (18). Although a Drosophila gene has been identified as being similar to the lymnokinin receptor in silico (18,19), no functional evidence for its identification as a leucokinin receptor is available nor is the similarity between Drosophila and Lymnaea leucokinins compelling (Table I).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although the first leucokinins were characterized in an insect (Holman et al, 1984), the first gene for a leucokinin receptor, and its cognate peptide, were identified in the pond snail Lymnaea stagnalis in a single, thoroughly impressive paper (Cox et al, 1997). Similarly, leucokinin signalling is known to occur in the Acari (mites and ticks) (Holmes et al, 2000). In insects, leucokinins are uniformly myogenic and diuretic (Coast et al, 2002).…”
Section: Rnai -Does It Promote 'Target' Species To 'Model' Status?mentioning
confidence: 99%
“…Periviscerokinin was the first conserved neuropeptide identified in ticks by using matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) analysis of single neurons (Neupert et al, 2005). Molecular cloning and functional analysis of the Gprotein-coupled receptor for a kinin-like peptide in the southern cattle tick, Boophilus microplus, further suggested that ticks produce multiple neuropeptides and receptors similar to those identified in other arthropods (Holmes et al, 2000(Holmes et al, , 2003Taneja-Bageshwar et al, 2006). We recently described the complex neuroendocrine network present in the central and peripheral nervous systems of the hard tick, Rhipicephalus appendiculatus, by using 15 different antibodies that recognize various neuropeptides (Šimo et al, 2009).…”
mentioning
confidence: 99%